CLINICAL, EPIDEMIOLOGICAL, AND LABORATORY CHARACTERISTICS OF ACUTE BRUCELLOSIS IN THE REPUBLIC OF UZBEKISTAN (ON THE EXAMPLE OF THE KASHKADARYA REGION) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Brucellosis is one of the most widespread zoonotic infections in the world with a high percentage of chronic forms, which accordingly negatively affects the economic component of the healthcare systems of countries with a high prevalence of brucellosis. The aim of our study was to determine the clinical, epidemiological, and laboratory characteristics of the course of acute brucellosis in the Republic of Uzbekistan, in particular in the Kashkadarya region. We examined 178 patients with clinical manifestations of acute brucellosis who sought medical care in regional medical institutions of the Kashkadarya region and republican clinics. Specific research methods were conducted by the ELISA method with the determination of IgM and IgG. Statistical processing of the research results was carried out using the programs "SPSS 20.0", "STATISTICA 6.0". Among patients with brucellosis, men predominate (75.00%), living in rural areas, which is due to the characteristics of the region associated with animal husbandry. It was established that acute brucellosis was 7.5 times more common among women aged 40 to 49 years (p